Hemichorea induced by a sphenoid ridge meningioma - Inoue, Hirotaka (Surg Neurol Int, 2021)
BACKGROUND: Movement disorders are rare in brain tumors. We describe a 45-year-old woman with hemichorea, a concomitant contralateral sphenoid ridge meningioma. CASE DESCRIPTION: The meningioma enlarged as her hemichorea worsened, and after meningioma resection, the hemichorea gradually subsided. N-isopropyl-p-[123I]-iodoamphetamine single-photon emission computed tomography performed preoperatively showed decreased regional cerebral blood flow (CBF) to the basal ganglia circuit ipsilateral to the tumor and, when repeated postoperatively, confirmed improved regional CBF. CONCLUSION: We propose that the enlarging sphenoid ridge meningioma had a remote effect on regional CBF and the thalamocortical motor center and that complex changes in the basal ganglia output may have caused the hemichorea.